Determining organizational resilience through employee resilient characteristics and supportive HR practices: The moderating effect of managerial resilience - Abdulrahman Awadh Aljuaid (PLoS ONE, 2025)
Resilience policies enable organizations to confront with adverse circumstances and ensure businesses operational continuity. Nevertheless, so far literature lacks how employee coping mechanism and supportive HR practices foster organizational resilience. Therefore, current study establishes research framework that combines factors such as employee resilience, psychological safety, problem focused coping, emotion focused coping, supportive human resource practices and workplace friendship and examine impact of these factors on organizational resilience. Similarly, this study has conceptualized moderating effect of managerial resilience between organizational resilience and organizational performance. The quantitative research design is taken into consideration. Data are collected through structured survey questionnaire. Overall, 421 respondents have participated in this organizational resilience research survey. These numerical responses are tested with structural equation modeling approach. Statistical results indicate that employee resilience, psychological safety, problem focused coping, emotion focused coping, supportive human resource practices and workplace friendship have depicted R 2 = 45.4% variance in organizational resilience. Therefore, constructs like organizational resilience and managerial resilience have shown R 2 =55.8% variance in organizational performance. Therefore, IPMA analysis has disclosed that emotion focused coping, employee resilience and managerial resilience are found most influential factors in measuring organizational resilience. This study has conceptualized employee coping mechanism towards organizational resilience and hence largely contributes to organizational resilience literature. To practice this study has suggested that factors such as employee resilience, psychological safety, problem focused coping, emotion focused coping and supportive human resource practices are crucial factors in improving organizational resilience and hence need policymakers attention. More precisely managers could enhance organizational resilience by improving employee emotion focused coping, employee resilience and managerial resilience. This research is original as it develops an amalgamated model that combines employee coping mechanism and supportive HR practices altogether to investigate organizational resilience. Likewise, the scope of this study is also ample as it collects observations from managers at border scale and test research framework with numerical data.